The financial culture of saving and investment in economic growth in the mi-cro and small companies of the city of Trujillo, year 2020 (SCIÉNDO INGENIUM, 2021)
The purpose of the research was to determine the influence of the financial culture of saving and investment on economic growth in micro and small companies in the city of Trujillo, year 2020. The methodology used was a descriptive, explanatory, causal correlational research, historical, non-experimental, and knowledge has been used through principles, norms, historical, economic data, which was applied to financial culture to measure the influence of economic development on MYPES. The population consisted of 20,000 micro and small businesses in the city of Trujillo. The sample consisted of 50 microenterprises at the discretion of the researcher, using random procedures and statistical techniques, through non-parametric sampling. It was concluded that there is a moderate positive correlation between the variables financial culture of savings and investment in the economic development of micro and small companies in the city of Trujillo, year 2020, having obtained a Pearson correlation coefficient of r = 0.692.
Keywords: Culture; financial culture; finance; savings; investment; economic growth; micro and small businesses